Healthy Pedagogy: Awakening of a New Node - Ileana Castillo Cedeño; Rocío Castillo Cedeño; Luz Emilia Flores Davis; Giselle Miranda Cervantes (Universidad Nacional, Costa Rica, 2014)
This paper intends to recover a pedagogic vision in life, as an experience and a process that dignifies joy, love, ecology, leisure, freedom and hope, as options that enable routes for a pedagogic project that generates health. The theoretical position is assumed as a holistic paradigm to conclude that the planetary crisis, that generates serious and persistent health problems at personal, social, and worldwide levels, can be modified using a healthy pedagogy which constitutes a creative, loving and hopeful challenge for the cohabitation of diverse life forms.  The term "Healthy Pedagogy" rises from the need to establish a dialogical relationship between pedagogy and health, based on renewed visions that lead to the rising of a new node. Both the right to health and the right to education are usually understood as independent from each other. However, the intersection between them can signify a great challenge and an important revelation.